2021
DOI: 10.1042/bsr20203020
|View full text |Cite
|
Sign up to set email alerts
|

Network-based approach to identify prognosis-related genes in tamoxifen-treated patients with estrogen receptor-positive breast cancer

Abstract: Tamoxifen is an estrogen receptor (ER) antagonist that is most commonly used for the treatment of ER-positive breast cancer. However, tamoxifen resistance remains a major cause of cancer recurrence and progression. Here, we aimed to identify hub genes implicated in the progression and prognosis of ER-positive breast cancer following tamoxifen treatment. Microarray data (GSE9893) for 155 tamoxifen-treated primary ER-positive breast cancer samples were obtained from the Gene Expression Omnibus database. In total… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Survival analysis from data obtained from publicly available datasets showed that high expression of the MAPT gene predicted favorable outcomes in ER-positive breast cancer [ 105 ]. Breast cancer cell lines and tissue samples confirmed the downregulation of MAPT in tamoxifen-resistant patients compared to the sensitive ones.…”
Section: Tau and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Survival analysis from data obtained from publicly available datasets showed that high expression of the MAPT gene predicted favorable outcomes in ER-positive breast cancer [ 105 ]. Breast cancer cell lines and tissue samples confirmed the downregulation of MAPT in tamoxifen-resistant patients compared to the sensitive ones.…”
Section: Tau and Cancermentioning
confidence: 99%
“…Breast cancer cell lines and tissue samples confirmed the downregulation of MAPT in tamoxifen-resistant patients compared to the sensitive ones. Gene set enrichment analysis strongly linked the MAPT gene to immune-related signaling pathways [ 105 ]. A possible role for Tau in glioblastoma by controlling 3D cell organization and functions via the PI3K/AKT signaling axis has also been recently suggested by Pagano and colleagues [ 106 ].…”
Section: Tau and Cancermentioning
confidence: 99%
“…GRSF1 is characterized by 3 RNA recognition motif (RRM) domains (which are responsible for RNA-binding), and participates in cancer progression via the mediation of microRNA-mediated gene expression ( 17 , 18 ). Previous research has shown that patients suffering from estrogen receptor–positive breast cancer with high levels of GRSF1 are more resistant to tamoxifen than those patients with low levels of GRSF1 ( 19 ). Notably, GRSF1 has been observed to facilitate the malignant behavior of cervical cancer cells by stimulating cancer-related signal pathways ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%